(3ehLg dWdHI GdSfI GdKGdKI djSGfS h WdHI GdeGSJQ TYHJj GdYdhe GdeGdjI h GdeMGSHjI h Ydhe GdJSjjQs - (3eMeO(B, (3MjeQGfs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2022)
1/(3OQGSGJ eMGSHjI eGdjI eYebI(B: (3eMGSHI GdGhQGb GdeGdjI, GdGZdaI, YbhO GdGjLGQ GdJehjdj,GdQhGJHh GdCLhQ,GdGgJdGcGJ h NSGFQ GdbjeI ddCUhd ZjQ LGQjI,NSGFQ GdbjeI ddeNRhfGJ h eMGSHI GdRHGFf (B2/(3OQGSGJ LHGFjI eYebI(B: (3GdVQjHI GdLRGajI GdhMjOI, GdVQjHI Ydi CQHGM GdTQcGJ , GdVQjHI Ydi GdONd GdELeGdj , GdQSe Ydi GdbjeI GdeVGaI h GdQSe Ydi GdfTGW Gdegfj(B.s
(3eQGLY U(B.193s
Keywords: (3GdLHGjIs; (3GdeMGSHIs